Enhanced interfacial interactions by PEEK-grafting and coupling of acylated CNT for GF/PEEK composites. (April 2020) - Zhu, Shu; Qian, Ying; Hassan, Elwathig A.M.; Shi, Rujing; Yang, Lili; Cao, Huajun; Zhou, Jianfeng; Ge, Dengteng; Yu, Muhuo
Abstract: The interfacial strength between glass fiber (GF) and polyetheretherketone (PEEK) matrix is relatively weak, thus mechanical performances of GF/PEEK composites prepared without surface modifications of GF are rather poor. In this study, we established an effective method to enhance interfacial interactions between GF and PEEK matrix by introducing dual compatibilizer of aminated PEEK and acylated carbon nanotubes (CNTs), which contributed to the increased compatibility, multiple interactions and mechanical interlocking between fibers and the matrix. The surface topographies, chemical compositions, wettability, and mechanical performances were investigated. As a result, the interlaminar shear strength (ILSS), tensile strength and modulus of modified GF/PEEK composite were obviously improved by 75% ( 35 MPa), 23% ( 338 MPa) and 12% ( 18 GPa), respectively. Such modification method based on chemical grafting shows great potential in manufacturing high-performance GF/PEEK composites containing continuous GF or GF fabrics in large scales. Graphical abstract: Image 1 Highlights: Proposed a modification method for enhancing interfacial interactions in GF/PEEK by introducing PEEK-NH2 & acylated CNT. Chemical bonding bridging was formed between GF and sizing agents which have similar chemical structures of PEEK matrix. ILSS and tensile strength of modified GF/PEEK composites improved by 75 % ( 35 MPa) and 23% ( 338 MPa), respectively.